2014
DOI: 10.1104/pp.113.232629
|View full text |Cite
|
Sign up to set email alerts
|

Two Rice Authentic Histidine Phosphotransfer Proteins, OsAHP1 and OsAHP2, Mediate Cytokinin Signaling and Stress Responses in Rice    

Abstract: Cytokinin plays an important role in plant development and stress tolerance. Studies of Arabidopsis (Arabidopsis thaliana) have demonstrated that cytokinin acts through a two-component system that includes a histidine (His) kinase, a His phosphotransfer protein (HP), and a response regulator. Phylogenetic analyses have revealed the conservation of His kinases but lineage-specific expansion of HPs and response regulators in rice (Oryza sativa). However, whether the functions of rice HPs have diverged remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 63 publications
3
59
0
2
Order By: Relevance
“…In wheat, the HKTs NAX1 and NAX2 fulfill similar roles (Lindsay et al, 2004). Shi et al (2002) suggested a similar role in xylem Na + reabsorption for the SOS1 transporter (depending on the level of salinity stress) but the evidence for this is less convincing.…”
Section: Na+ Uptake and Distributionmentioning
confidence: 99%
“…In wheat, the HKTs NAX1 and NAX2 fulfill similar roles (Lindsay et al, 2004). Shi et al (2002) suggested a similar role in xylem Na + reabsorption for the SOS1 transporter (depending on the level of salinity stress) but the evidence for this is less convincing.…”
Section: Na+ Uptake and Distributionmentioning
confidence: 99%
“…Abiotic stresses, such as drought and high salinity, negatively impact plant growth and agricultural productivity. Plants have evolved to cope with adverse environments by a variety of strategies at the molecular, metabolic, cellular, physiological, and morphological levels (Jiang, Belfield, Cao, Smith, & Harberd, ; Martínez‐Atienza & Quintero, ; Nakabayashi et al, ; Sun et al, ). For example, reactive oxygen species (ROS), including superoxide radicals O 2˙ − , hydrogen peroxide H 2 O 2 , and hydroxyl radicals ˙OH, are accumulated under stress conditions, including high salinity and drought (Mittler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of KNOTTED1-like results in high-CK and low-GA and inhibits root development by inducting OsIPT2 and OsIPT3 expression (Sakamoto et al, 2006). Similarly, down-regulation of CK signaling leads to reduced internode lengths and tiller number, and promoted lateral root growth (Sun et al, 2014). Thus, the appropriate GAs and CKs homeostasis is required for the normal growth and development in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressing ISOPENTENYLTRANSFERASE could lead to high CKs levels and improve drought tolerance by coordinating source/sink relationships and nutrient metabolism in rice (Peleg et al, 2011; Reguera et al, 2013). Similarly, OsAHP1 and OsAHP2 function as positive regulators of the cytokinin signaling and are required for the regulation salt and drought tolerance in rice (Sun et al, 2014). These findings show that GA and CK play antagonistic roles in plant response to abiotic stresses, and manipulating GA and CK levels is an effective strategy to improve stress tolerance in rice.…”
Section: Discussionmentioning
confidence: 99%